The Islamic Leadership Style of Principals in Building a Religious School Culture in Public Senior High Schools in Jambi Province - Ari Zumardin; Marwazi; Iskandar (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study examines the implementation of religious school culture and the Islamic leadership style of principals in public senior high schools in Jambi Province, Indonesia. Using a qualitative phenomenological approach, data were collected through observations, in-depth interviews, and document analysis involving principals, vice principals, teachers, and students at SMA Negeri 1 Jambi City and SMA Negeri 1 Sungai Penuh. The findings reveal that religious culture is implemented through various daily, weekly, and annual activities, including congregational prayers, Qur’anic recitation, Faith and Piety Development programs, Tahfiz activities, and other religious character-building initiatives. The study also found that principals demonstrate an Islamic leadership style characterized by exemplary behavior, participation, integrity, responsibility, and commitment to religious values. These leadership practices contribute significantly to strengthening students’ religious awareness, discipline, and moral character while fostering a positive school environment. Despite challenges such as limited facilities, inconsistent teacher participation, and diverse student backgrounds, the implementation of religious culture has been effective in supporting character development. The study concludes that Islamic leadership plays a crucial role in establishing and sustaining a religious school culture and contributes to achieving national educational goals by developing students who are religious, ethical, and socially responsible.